TINJAUAN YURIDIS TERHADAP PUTUSAN TINDAK PIDANA PEMBERIAN KETERANGAN PALSU KEDALAM SURAT AKTA OTENTIK - Sri Karsina Ramadhan (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACKSRIKARSINA RAMADHAN (13.11.1001.1011.286), Juridical Review Against Criminal Decision Falsification Letter In Authentic Deed is Guided by Dr. H. Irman Syahrial, SH., M.Hum as the guidance of I and H. Syamsudin, SH., M. Hum as the guidance II. This study aims to determine the application of criminal law against perpetrators of authenticity of the Deed and to know the judge's consideration in imposing criminal sanctions against the perpetrators of Authenticity fraud. Research conducted by the author on "Juridical Review of Criminal Decision Fraud Letter in Authentic Deed" then the authors do research through the existing literature, especially legislation related to the material from the writing of the thesis, as well as research into the library and take the example Cases through internet / websites that already have a verdict. The results achieved in this study indicate that, the application of criminal law against the Crime Falsification of Authentic Deed is in accordance with the provisions of the material criminal law as regulated in Article 266 Paragraph (1) of the Criminal Code Jo. Article 55 Paragraph (1) of the Criminal Code. The application of criminal provisions to the Crime of Authenticity of Authentic Deeds is based on legal facts both through witness statements, the statements of the accused and the evidence, in addition, also based on the juridical consideration of the Prosecutor's indictment and prosecution. Whereas the judge's consideration in imposing criminal sanctions against perpetrators of Authenticity Counterfeiting has been appropriate based on the elucidation of witnesses' statements, statements of defendants, and evidence, and taking into account relevant laws reinforced by the Judge's conviction.Keyword : Authentic deed forgery, Application of criminal law, Judge consideration